Analisis Pengaruh Environmental Cost Dan Effective Tax Rate Terhadap Nilai Perusahaan Subsektor Batubara Yang Terdaftar Di Bursa Efek Indonesia (Periode 2020-2024) - Apriliando Al'nurdinsyah; Lilis Lasmini; Novy Trianthy Noegraha (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine the impact of environmental costs and effective tax rates on the firm value of companies in the coal subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using secondary data and purposive sampling, yielding 100 observations from 20 companies. The results show that environmental costs have a significant negative effect, while the effective tax rate has no significant effect on firm value. These findings indicate that external factors, such as macroeconomic dynamics and fluctuations in global commodity prices, are more dominant in influencing firm value than internal factors.